Islamic Boarding School based vocational education: a case study on SMK Syubbanul Wathon Tegalrejo Magelang - Umi Rochayati; Z. Zamroni; Putu Sudira (Jurnal Pendidikan Vokasi, 2017)
This study aims to: (1) describe the conception of vocational education by the Islamic boarding school community; (2) describe the education system at SMK Syubbanul Wathon Tegalrejo Magelang. The study was conducted at SMK Syubbanul Wathon Tegalrejo Magelang using qualitative approach of a case study. The data collection used interviews, participant observation, and documents. The research informants consisted of the chairman of the foundation of Syubbanul Wathon, the caretakers, the principal, the vice principal, the teachers, the cleric, and the students. The results of the study were: (1) The conception of vocational education by Islamic Boarding School community is ngluru ngilmu which means sincerity between teachers and students, (2) The system of vocational education based on Islamic boarding school in SMK Syubbanul Wathon Tegalrejo Magelang include: (a) the context: SMK Syubbanul Wathon Tegalrejo Magelang has internalized the dynamics of context into formulation of school vision, mission, goals, and activities; (b) input: SMK Syubbanul Wathon Tegalrejo Magelang applies KTSP and Islamic boarding school curriculum; (c) process, SMK Syubbanul Wathon Tegalrejo Magelang integrates the school and Islamic boarding school system; (d) output, SMK Syubbanul Wathon Tegalrejo Magelang graduates have vocational skills, strong religiosity, independence, discipline and skills in foreign languages; (e) outcome: 44% of SMK Syubbanul Wathon Tegalrejo Magelang graduates worked, 42% went to college, and 14% went to salaf boarding school or entrepreneurship.